Controlling proteolysis of Clp peptidase: a possible target for combating mitochondrial diseases - da Silva, Ronivaldo Rodrigues [UNESP] (2019)
Some mechanisms of cellular stress, aging, and apoptosis are related to proteolysis. With respect to ClpP, little is known about the mechanical manner in which the substrate is hydrolyzed in and released from the degradation chamber. Furthermore, what would be the real influence of ClpP in mammalian UPR mt ?